Does electronic government deter corruption? Evidence from across the world - Martins, João (2021)
Electronic government innovations are one of the most important changes in public administration in recent years. Governments in many countries have implemented e-government policies to foster efficiency and transparency, and to mitigate corruption. This paper explores the effects of e-government on corruption using longitudinal data for more than 170 countries for the period 2002-2017. Empirical results strongly support the hypothesis that e-government can be used to deter corruption. This result is robust to alternative indicators of corruption and e-government, as well as to a variety of estimation techniques. A novelty of our research is that we analyse under which conditions is e-government more effective in reducing corruption. Quantile regressions indicate that the potential of e-government to deter corruption is higher between quantiles 0.3 to 0.8 of the corruption distribution. E-government also reveals to be a more effective corruption deterrent in countries that are not classified as high-income countries and that are not in the extremes of the freedom of the press variable distribution.